APPLICATION OF ZEOLITE IN INDUSTRIES AND ENVIRONMENTS - Thamzil Las; Husen Zamroni (Institut Teknologi Bandung, 2002)
Zeolites are crystalline, hydrates of alumino-silicate mineral with a three-dimensional framework structure which are occured in Indonesia as large deposits in the form of near-pure minerals and of low cost. In recent years, many scientist have focused their research to develop these minerals to be used in science and technology applications. Because of their unique crystal structure, zeolites have the importance properties of sorption, ion-exchange, molecular sieving and catalysis, which enable to them to be used in various industrial processes, waste management and environmental pollution problems. This paper describes the prospect of clinoptilolite and mordenite, which have been investigated in many laboratories, to be considered for their utilization in the industries and environmental management.